Factor affecting consumers' perception towards electronic payment: case study in Segamat, Johor / Muhammad Pahrolrozi Sa'rani - Sa'rani, Muhammad Pahrolrozi (Faculty of Business and Management, 2019)
Electronic payment systems are considered as e-commerce backbone and one of the most important aspects. It can be defined as a payment service that uses information and communications technology including integrated circuit card, cryptography, and telecommunications network. This study aims to identify factors that influence the perception of electronic payments from the perspective of Malaysian consumers in Segamat, Johor. Malaysia is moving towards greater acceptance of e-payment, but majority of online population in Malaysia is still consider "infants" with a low level of internet knowledge, it will build up fears of using e-payment. This study will use primary data. Data will be collected through the distribution of questionnaires among respondents in Segamat. The dependent variable is perception towards e-payment and the independent variables that will be used in this research are benefits, trust, and self efficacy, ease of use, security and risk. The sample size for this study is 100 respondents in Segamat. The simple random sampling technique will be used to distribute the questionnaire to the respondents. The data will be regressed using the Statistical Program for Social Science. This research will provide an idea of the factors that influence the perception of consumers regarding electronic payments in Segamat.